2020
DOI: 10.1002/jdd.12437
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the use of magnifying dental loupes on the performance of undergraduate dental students undertaking simulated dental procedures

Abstract: Objectives This study aimed to evaluate the impact of the use of magnification (2.5x dental loupes) for third‐year dental students in simulated endodontics and fixed prosthodontics assessments compared to those using no magnification. Methods Upon institutional review board exemption, third‐year dental students were assessed during endodontics and fixed prosthodontics exams in the simulation laboratory. The endodontic group (n = 93) consisted of students who made an endodontic access preparation on a plastic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…Most students in our sample who chose to use magnifying dental loupes perceived that the quality of their work has improved. Like previous studies, we observed significant improvement in the scores of students that used magnifying dental loupes at the end of the studied period [16][17][18]. In this study, students were not aware of each's other scores.…”
Section: Discussionsupporting
confidence: 79%
“…Most students in our sample who chose to use magnifying dental loupes perceived that the quality of their work has improved. Like previous studies, we observed significant improvement in the scores of students that used magnifying dental loupes at the end of the studied period [16][17][18]. In this study, students were not aware of each's other scores.…”
Section: Discussionsupporting
confidence: 79%
“…1 Assistant Professor and Consultant of Restorative and Digital Dentistry, Restorative Dentistry Department, King Abdul-Aziz University, Faculty of Dentistry, Jeddah, Saudi Arabia. 2 Assistant Professor and Prosthodontist, Oral Diagnostic Sciences Department, King Abdul-Aziz University, Faculty of Dentistry, Jeddah, Saudi Arabia. success of challenging esthetic restorative and endodontic operations (Braga et al, 2021).…”
Section: Medical Sciencementioning
confidence: 99%
“…2 Assistant Professor and Prosthodontist, Oral Diagnostic Sciences Department, King Abdul-Aziz University, Faculty of Dentistry, Jeddah, Saudi Arabia. success of challenging esthetic restorative and endodontic operations (Braga et al, 2021). Dentists frequently use magnifying loupes for clinical practice and dental students are increasingly seen wearing them while learning (Eichenberger et al, 2011).…”
Section: Medical Sciencementioning
confidence: 99%
“…Improving the visibility of small details using loupes contributes to the detection of clinical errors, such as problems with marginal sealing, marginal leakage, and secondary caries [7][8][9] . Studies have shown that using loupes improved the quality of tooth preparation [10][11][12][13] .…”
mentioning
confidence: 99%